A new gene order in the mitochondrial genome of the deep-sea diaphanous hatchet fish Sternoptyx diaphana Hermann, 1781 (Stomiiformes: Sternoptychidae). Issue 3 (2nd July 2020) - Arrondo, Nair Vilas; Gomes-dos-Santos, André; Román Marcote, Esther; Pérez, Montse; Froufe, Elsa; Castro, L. Filipe C.
Abstract: Species of the Sternoptychidae teleost family display an impressive morphology, including their extreme reduced size. Here, we report the first mitochondrial genome of the diaphanous hatchet fish Sternoptyx diaphana . By using short-read sequencing Illumina HiSeq, we generated two mitochondrial contigs which were later physically assembled by PCR. The mitochondrial genome of S. diaphana was 17, 224 bp in length (excluding the control region) and is composed of 13 PCGs and 2 ribosomal RNA genes. Strikingly, we could not identify the tRNA-Phe and two copies of tRNA-Met were differently positioned. Additionally, the mitogenome displays a completely new gene rearrangement among vertebrates. We expect that the study presented here will pave the way for further molecular studies with this underrepresented group of illusive teleost fish.